Detection of 17-α-ethinylestradiol with bio-functionalized tapered optical fiber sensor - Hamid, Rosyati; Mustapha Kamil, Yasmin; Aris, Ahmad Zaharin; Abu Bakar, Muhammad Hafiz; Suhailin, Fariza Hanim; Alresheedi, Mohammed Thamer; Ng, Eng Khoon; Mahdi, Mohd Adzir (Elsevier, 2024)
This paper presents the utilization of tapered optical fiber (TOF) biosensor for the detection of 17-α-ethinylestradiol (EE2), an estrogen hormone. TOF with a waist diameter of 12 μm was fabricated from single mode fiber using heat and pull method. The tapered area was used as the sensing interface between the evanescent waves propagating around the fiber due to its unique geometry and the attached molecules on the tapered surface. EE2 antibodies were used as biorecognition molecules towards the targeted analyte, EE2. When tested with different concentrations of EE2 within the range of 0.1 ng/L – 1 mg/L, the developed sensor attained a detection limit of 1 ng/L with a sensitivity value of 1.088 nm/ngL-1 within the operation range of 1 – 10 ng/L. The specificity of the sensor was validated by testing the developed sensor with estrone (E1) and no significant wavelength shift was observed. These findings highlight the potential of our approach for sensitive and selective detection of EE2.